Problems of Legal Regulation of Academic Integrity Compliance in Ukraine - O. V. Bernatskyi (Bulletin of Kharkiv National University of Internal Affairs)
The current state of legal regulation of academic integrity in Ukraine has been analyzed. It has been found out that the standards of academic integrity are still poorly studied in the scientific field in Ukraine. However, some aspects of the legal regulation of academic integrity have already been considered in the works of national scholars. However, given the relative novelty of the term of “academic charity” in the current legislation, a number of issues of legal regulation of academic integrity in Ukraine remain relevant and unresolved.